Analisis Peran PKN Terhadap Mahasiswa FIS Unimed dalam Memahami Hak dan Kewajiban Sebagai Warga Negara - Kania Nova Ramadhani; Esra Natasya Br Sitepu; Gadis Prasiska Sembiring; Al Firman Mangunsong; Ramsul Nababan (LPPM Politeknik Pratama, 2023)
This study aims to identify and analyze how FIS UNIMED students understand the rights and obligations of citizens and find out what challenges are faced in understanding the rights and obligations of citizens. The research method used is qualitative research. The research location is Medan State University. Data were collected through interviews with students of the faculty of social sciences consisting of anthropology majors, history majors, geography majors and Civics majors. And document analysis related to the curriculum and learning models applied. The results showed that FIS UNIMED students have understood the rights and obligations as citizens but there are several challenges or obstacles faced by FIS UNIMED students. This research provides in-depth insight into the challenges faced by students in understanding the rights and obligations of citizens. The implications of these findings can be used as a basis for developing better educational policies and implementing more effective strategies in facilitating Civics learning as a forum for understanding the rights and obligations of citizens.